SCREENING OF LIPASE FROM WATER BACTERIA IN BENANGA LEMPAKE DAM, NORTH SAMARINDA AND ITS POTENTIAL AS A DETERGENT ADDITIVE - Vera, Hendrica Mini; Astuti, Winni; Pratiwi, Djihan Ryn (Jurusan Kimia FMIPA UNMUL, 2023)
Lipase is an enzyme that can hydrolyze triglycerol into glycerol and free fatty acids. The aim of this research is to obtain lipase-producing bacteria and determine the potential of lipase from water bacteria in the water of the Benanga Lempake Dam, North Samarinda for biodetergent applications through stability test of lipase activity against several commercial detergents. Screening of lipase-producing bacteria was carried out on nutrient agar media containing olive oil and Rhodamine B. The results showed that seven isolates were capable of producing lipase. Based on the stability test of lipase on detergent, it can be seen that the activity of lipase decreased by more than 70% at the addition of 1% detergent.